Students’ Perceptions of Utilizing PBL (Project-Based Learning) Method and Using Video in Writing Narrative Texts - Fauzia utamie , Mega Dinie; Ruswandi, Riki; Saili Rahmah , Leni (Institut Agama Islam Negeri Palopo, 2025)
The application of a Project-Based Learning (PBL) strategy and the use of video as a teaching medium for narrative writing are the main objectives of this project. The objective is to gauge the method's efficacy by looking at how grade XI students at SMA Negeri 21 Bandung perceive it. The study employs a survey design and a quantitative methodology. Descriptive statistical analysis and a questionnaire with a 5-level Likert scale were used to gather data. The validity and reliability of the research tool have been examined (Cronbach's Alpha = 0.906). The results showed that most students positively perceived PBL and video media, with an average score above 3.47 (